Nanoporous membrane fabrication by nanoimprint lithography for nanoparticle sieving. Issue 4 (21st January 2022) - Sabirova, Ainur; Florica, Camelia F.; Pisig, Florencio; Syed, Ahad; Buttner, Ulrich; Li, Xiang; Nunes, Suzana P.
Abstract : An isoporous membrane with strictly controlled pore size, shape and distribution could provide an efficient, precise and mild sieving of particles in nanotechnology and biomedical applications. Abstract : An isoporous membrane with strictly controlled pore size, shape and distribution could provide an efficient, precise and mild sieving of particles in nanotechnology and biomedical applications. However there is a lack of highly porous polymeric membranes combining isoporosity and high permeance in the range below 500 nm. Track-etched membranes are practically the only commercial option. Membranes prepared by phase inversion typically have a broad pore size distribution. Most nanofabrication methods have limited the preparation of membranes with pores in the micrometer range. In this work, we present a nanotechnology-based fabrication methodology to manufacture a stable and flexible nanoporous polymeric membrane with 300 nm isopores using UV nanoimprint lithography. The highly porous membrane has a pore density of 4 × 10 9 pores per cm 2 and stable permeance of 108 000 L m −2 h −1 bar −1 . Uniform ZIF-8 nanoparticles were synthesized and the isoporous membrane successfully demonstrated as high as 100% rejection and size-based sieving performance of nanoparticles.